Preparing today's students for tomorrow's jobs in Metropolitan America - Perna, Laura W. (City in the twenty-first century book series., 2013)
Education, long the key to opportunity in the United States, has become simply essential to earning a decent living. By 2018, 63 percent of all jobs will require at least some postsecondary education or training. Teachers and civic leaders stress the value of study through high school and beyond, but to an alarmingly large segment of America's population-including a disproportionate number of ethnic and racial minorities-higher education seems neither obtainable nor relevant. Preparing Today's Students for Tomorrow's Jobs in Metropolitan America, edited by Laura W. Perna, offers useful insights into how to bridge these gaps and provide urban workers with the educational qualifications and skills they need for real-world jobs.Preparing Today's Students for Tomorrow's Jobs in Metropolitan America probes more deeply than recent reports on the misalignment between workers' training and employers' requirements. Written by researchers in education and urban policy, this volume takes a comprehensive approach. It informs our understanding of the measurement and definition of the learning required by employers. It examines the roles that different educational sectors and providers play in workforce readiness. It analyzes the institutional practices and public policies that promote the educational preparation of today's students for tomorrow's jobs. The volume also sheds light on several recurring questions, such as what is the "right" amount of education, and what should be the relative emphasis on "general" versus "specific" or "occupational" education and training?Ensuring that today's students have the education and training to meet future career demands is critical to the economic and social well-being of individuals, cities, and the nation as a whole. With recommendations for institutional leaders and public policymakers, as well as future research, this volume takes important steps toward realizing this goal.